2015
DOI: 10.1179/1743289814y.0000000121
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal crystallisation of polypropylene/hollow glass microspheres composites

Abstract: Polypropylene/hollow glass microspheres composites were prepared by melt blending. The nonisothermal crystallisation of the polypropylene (PP) and its composites were investigated via differential scanning calorimeter (DSC). The results showed that the crystallisation peaks shifted to lower temperature and the exothermic trace became wider when the cooling rate was increased. Moreover, the hollow glass microspheres caused an increase in both the crystallisation and initial crystallisation temperatures. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Liang [7] et al examined the thermal properties of HGM-filled PP composites with different densities and different volume fractions. Li [38] et al prepared HGM-filled PP composites with different mass fractions and studied their non-isothermal crystallization behavior. The authors found that the HGM with modification resulted in lower peak crystallization temperature and lower initial crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Liang [7] et al examined the thermal properties of HGM-filled PP composites with different densities and different volume fractions. Li [38] et al prepared HGM-filled PP composites with different mass fractions and studied their non-isothermal crystallization behavior. The authors found that the HGM with modification resulted in lower peak crystallization temperature and lower initial crystallization temperature.…”
Section: Introductionmentioning
confidence: 99%